Fungsi Satuan Tugas Sapu Bersih Pungutan Liar di Kota Kupang : (Studi Kasus Pelabuhan Tenau) - Fadel Dwiputra Ali Saini; Yosef M. Monteiro; Cyrilius W. Taran Lamataro (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The formation of the Saber Pungli Task Force was carried out as a firm and real step by the government to restore public trust, so that through Presidential Regulation Number 87 of 2016 concerning the Clean Sweep Task Force for Illegal Levies, all city areas in Indonesia formed the task force to eradicate and enforce the law. This type of research is empirical. After the data is obtained, the researcher will group the data based on the data source and analyze it to get answers to the formulation of the problem in this study. The results of the study show that the Clean Sweep Task Force for Illegal Levies (Satgas Saber Pungli) was formed with the aim of eradicating the practice of illegal levies that occur in various public service sectors in Indonesia, and the Clean Sweep Task Force for Illegal Levies at Tenau Port involves various activities aimed at overcoming and preventing the practice of illegal levies in various public service sectors to create a public service system that is free from extortion and increase public trust in public services. In its implementation, various inhibiting factors are still encountered, namely the weak performance of the task force in the field, aspects of facilities and infrastructure such as the low reporting channels that are friendly and easily accessible to the public, and the budget which is still a real challenge in implementing the Saber Pungli Task Force function, especially in areas such as East Nusa Tenggara Province (NTT) which has geographical characteristics as an archipelago.